Mysteries of moons and moon phases - Labrecque, Ellen (2021)
"Full moons in folklore and legends are said to have magic power. Does a full moon really affect our planet and people living on it? Get a closer look at the moons in our solar system, from the known moons to the ones that haven't been discovered. Budding astronomers will learn all about moons, from Jupiter's 63 moons to the features of Earth's moon"--
The power of the moon -- The moon's orbit -- Shape-shifter -- The way of the tide -- Other moons -- The future of the moon.
Includes bibliographical references.
Ages 8-11
Grades 4-6
Keywords: Tides -- Juvenile literature; Satellites -- Juvenile literature; Moon -- Juvenile literature; Moon -- Phases -- Juvenile literature